Efficacy of microbial sampling recommendations and practices in sub-Saharan Africa. (1st May 2018) - Taylor, David D.J.; Khush, Ranjiv; Peletz, Rachel; Kumpel, Emily
Abstract: Current guidelines for testing drinking water quality recommend that the sampling rate, which is the number of samples tested for fecal indicator bacteria (FIB) per year, increases as the population served by the drinking water system increases. However, in low-resource settings, prevalence of contamination tends to be higher, potentially requiring higher sampling rates and different statistical methods not addressed by current sampling recommendations. We analyzed 27, 930 tests for FIB collected from 351 piped water systems in eight countries in sub-Saharan Africa to assess current sampling rates, observed contamination prevalences, and the ability of monitoring agencies to complete two common objectives of sampling programs: determine regulatory compliance and detect a change over time. Although FIB were never detected in samples from 75% of piped water systems, only 14% were sampled often enough to conclude with 90% confidence that the true contamination prevalence met an example guideline ( ≤ 5% chance of any sample positive for FIB). Similarly, after observing a ten percentage point increase in contaminated samples, 43% of PWS would still require more than a year before their monitoring agency could be confident that contamination had actually increased. We conclude that current sampling practices in these settings may provide insufficient information because they collect too few samples. We also conclude that current guidelines could be improved by specifying how to increase sampling after contamination has been detected. Our results suggest that future recommendations should explicitly consider the regulatory limit and desired confidence in results, and adapt when FIB is detected. Highlights: Analyzed microbial water quality sampling practices in 351 piped systems in sub-Saharan Africa. Many systems detected no indicator bacteria but tested too few samples to be confident in results. Sampling recommendations should consider definitions, limits, and confidence levels. These results can be used to improve international guidelines for water quality monitoring.